Peningkatan Kapasitas Bandwidth Menggunakan Teknologi Dwdm Ciena 6500 pada Sistem Kabel Bawah Laut Sea-Us - Iryanto, Mokhamad Trihandoyo; Kartawidjaja, Maria Angela (Universitas Pamulang, 2025)
This article discusses the process of increasing bandwidth capacity in the SEA-US submarine cable system using Dense Wavelength Division Multiplexing (DWDM) technology, specifically the Ciena 6500 device. DWDM technology enables simultaneous transmission of multiple optical signals within a single optical fiber, thereby enhancing network capacity without additional physical infrastructure. This study includes the stages of survey, installation, and testing of the device to ensure performance meets standards. The results show that the system was successfully upgraded with adequate technical parameters and without errors during the Integrated Test Set (ITS) testing. These findings demonstrate the effectiveness of DWDM technology in addressing the growing demand for bandwidth. Keywords: Bandwidth; DWDM; Ciena 6500; Submarine Cable, SEA-US